Pendampingan Penyusunan Laporan Keuangan dan Pajak Pondok Pesantren Baitul Qur’An Berbasis Excel - Sinarti Sinarti; Riri Zelmiyanti; Doni Putra Utama; Nanik Lestari; Muhammad Ikhlash (Jurnal Abdimas Adpi Sosial dan Humaniora, 2023)
The Baitul Qur'an Islamic Boarding School has resources that come from the participation of the community, government and donors so that good and transparent financial reports are needed for the Islamic boarding school's accountability for the resources entrusted to it. So the purpose of this study is to compile financial and tax reports for the Baitul Qur'an Islamic Boarding School in accordance with the Islamic boarding school accounting guidelines (PAP). This service is a continuation of the previous type of qualitative research activities with descriptive methods. This service uses two types of data, namely primary and secondary data. Data collection methods used are interviews, observation, and documentation. The result of this dedication is that the financial reports made by the Baitul Qur'an Islamic Boarding School are relatively simple, which only record cash disbursements and receipts which are inputted with the help of a computer. So that the Baitul Qur'an Islamic Boarding School has not implemented the Islamic Boarding School Accounting Guidelines.